The Impact of Orientalism upon the Path of Contemporary Arab Art - كيسو, فصيح (Latakia University Journal -Engineering Sciences Series, 2021)
The research examines the term "Orientalism", after Edward Said published his book "Orientalism", and discuss one of the 20th century contemporary cultural conflicts, and the impact of this term on Arab art production. How this term helped stereotyping and marginalizing contemporary Arab arts and how have impacted negatively on the subjects and the directions of contemporary Arab art. Knowing that the painting of "Orientalists" artists reflect the way that Europeans view of the East and its icons, this research will examine the important and the need to reclaim those icons. It answers various questions related to the nature of contemporary Arab art and its relationship to culture, history and theory. It will examine how the images about the Arab world appear in a new representational form through Western media, and also study the rise of new way of Orientalism and new colonialism.